PSYCHOLOGICAL COMPETENCE OF A TEACHER AS A FACTOR OF INCREASING THE EFFICIENCY OF INTERPERSONAL INTERACTION IN THE EDUCATIONAL ENVIRONMENT (Psychology Travelogs, 2025)
The article is devoted to the theoretical and analytical study of psychological competence as a key factor influencing the effectiveness of future education professionals. Contemporary education systems require future specialists not only to possess profound professional knowledge but also to demonstrate a high level of psychological competence, which ensures the efficiency of their professional activities. Teaching involves intensive communication, rapid adaptation to changes in the educational environment, conflict resolution, and the promotion of students’ holistic development. Therefore, a teacher’s ability to understand their own psychological characteristics and those of others, and to apply psychological knowledge in practice, becomes a crucial determinant of professional success. The article analyzes the structure of professional activity in education, emphasizing its multifunctionality, emotional intensity, and reliance on subject-subject interaction, dialogue, and partnership. Psychological competence is considered integral to professional effectiveness, encompassing the ability to understand students’ individual characteristics, regulate one’s own emotions, establish constructive communication, prevent and resolve conflicts, and create a favorable psychological environment for learning. Teachers with high psychological competence are capable of empathy, individualized teaching, classroom management, and fostering psychological safety, which positively impacts learning and developmental outcomes. The study concludes that psychological competence is a decisive factor in the effectiveness of future educators’ professional activities. Further research could focus on exploring the relationship between psychological competence and the personal and professional growth of teachers, as well as investigating its application in remote and blended learning contexts.
Keywords: psychological competence; professional activity; future educators; pedagogical effectiveness; self-regulation; interpersonal interaction